2021
DOI: 10.52628/87.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of open tibia fractures in Sub-Saharan African countries : a systematic review

Abstract: Open tibia fracture (OTF) treatment is well documented in developed countries. Yet, this fracture pattern remains challenging because it is associated with an increased risk of infection and delayed union, particularly in case of Gustilo III B and C open fractures. Since access to healthcare is limited in Sub- Saharan African countries, this paper explores the results of OTF management in this setting. A systematic review of the literature was conducted using current databases such as MEDLINE, Cochrane, EMBAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Staphylococci were the only Grampositive bacteria isolated in which 17 (23.3%) isolates comprised of 14 (19.2%) Staphylococcus aureus and 3 (4.1%) isolates were Coagulase negative Staphylococci (CoNS) (Table 3). (9), the present study found 100% of open tibial shaft fractures in the study population were managed with either external fixators or interlocking intramedullary nails. This is striking in view of known complications with cast immobilization compared to surgical fixation.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Staphylococci were the only Grampositive bacteria isolated in which 17 (23.3%) isolates comprised of 14 (19.2%) Staphylococcus aureus and 3 (4.1%) isolates were Coagulase negative Staphylococci (CoNS) (Table 3). (9), the present study found 100% of open tibial shaft fractures in the study population were managed with either external fixators or interlocking intramedullary nails. This is striking in view of known complications with cast immobilization compared to surgical fixation.…”
Section: Resultsmentioning
confidence: 59%
“…Gustilo II and III fractures were associated with higher risk of complications and the overall rate of infection was 30%. Malunion, chronic osteomyelitis and nonunion were observed in 14.5%, 12.3% and 7% of the cases, respectively (9).…”
mentioning
confidence: 95%
“…The implementation of the EZExFix provides a solution to these challenges, eliminating the dependency on healthcare facilities altogether. The EZExFix is made with materials that reduce the cost and allow local production in order to increase accessibility also for developing countries that are in need of easy accessible stabilization methods [41][42][43]. The EZExFix could be also considered for inclusion in a medical kit because it is compact, portable (requires only a battery for the drill; no external power supply needed), lightweight (1 kg without the drill), and takes up minimal space (35 × 20 × 10 cm, maximum of a shoebox) in the limited resources available such as on a spacecraft.…”
Section: Discussionmentioning
confidence: 99%
“…During intraoperative, fracture fixation and surgical debridement of dead tissues is done. [7] Successful management of fractures postsurgery entails tissue closure, rehabilitation practices, pain management, and antibiotic prophylaxis. This approach can improve outcomes, including chronic pain and postoperative complications such as nonunion and bone infections.…”
Section: Introductionmentioning
confidence: 99%